Body mass estimation in hominoids: Age and locomotor effects. Issue 115 (February 2018) - Burgess, M. Loring; McFarlin, Shannon C.; Mudakikwa, Antoine; Cranfield, Michael R.; Ruff, Christopher B.
Abstract: While there are a number of methods available for estimation of body mass in adult nonhuman primates, very few are available for juveniles, despite the potential utility of such estimations in both analyses of fossils and in museum collection based research. Furthermore, because of possible scaling differences, adult based body mass estimation equations may not be appropriate for non-adults. In this study, we present new body mass estimation equations for both adult and immature nonhuman hominoids based on joint and metaphyseal dimensions. Articular breadths of the proximal and distal femur, distal humerus and tibial plateau, and metaphyseal breadths of the distal femur and humerus were collected on a reference sample of 159 wild Pan, Gorilla, Pongo, Hylobates, and Symphalangus specimens of known body mass from museum and research collections. Scaling of dimensions with body weight was assessed in both the adult and the ontogenetic sample at several taxonomic levels using reduced major axis regression, followed by regression of each dimension against body mass to generate body mass estimation equations. Joint dimensions were found to be good predictors of body mass in both adult and immature hominoids, with percent prediction errors of 10–20%. However, subtle scaling differences between taxa impacted body mass estimation, suggesting that phylogeny and locomotor effects should be considered when selecting reference samples. Unlike patterns of joint growth in humans, there was little conclusive evidence for consistently larger joints relative to body mass in the non-adult sample. Metaphyseal breadths were strong predictors of body mass and, with some exceptions, gave more precise body mass estimates for non-adults than epiphyseal breadths.